Promoting Employment-Intensive Growth in Sri Lanka: Policy Analysis of the Manufacturing and Service Sectors - Chandrasiri, Sunil (My University, 2010)
The purpose of this paper is to examine the employment effect of growth in manufacturing sector industriesin Sri Lanka covering a period of 17 years from 1990. In the main text, two periods are distinguished interms of employment elasticity: a) the slow growth period of the 1990s and b) the period of high growth (post-2000). The paper uses an integrated framework which qualifies the relative importance of the key factors determiningemployment elasticity and its variations between the two time periods. The findings indicate that themanufacturing sector has responded positively to policy reforms of the post-1977 period in terms of growth,export orientation, productivity, profitability and employment creation.